3D echocardiographic analysis of aortic annulus for transcatheter aortic valve replacement using novel aortic valve quantification software: Comparison with computed tomography. Issue 5 (27th March 2017) - Mediratta, Anuj; Addetia, Karima; Medvedofsky, Diego; Schneider, Robert J.; Kruse, Eric; Shah, Atman P.; Nathan, Sandeep; Paul, Jonathan D.; Blair, John E.; Ota, Takeyoshi; Balkhy, Husam H.; Patel, Amit R.; et al.
Abstract : Background: With the increasing use of transcatheter aortic valve replacement (TAVR) in patients with aortic stenosis (AS), computed tomography (CT) remains the standard for annulus sizing. However, 3D transesophageal echocardiography (TEE) has been an alternative in patients with contraindications to CT. We sought to (1) test the feasibility, accuracy, and reproducibility of prototype 3DTEE analysis software (Philips) for aortic annular measurements and (2) compare the new approach to the existing echocardiographic techniques. Methods: We prospectively studied 52 patients who underwent gated contrast CT, procedural 3DTEE, and TAVR. 3DTEE images were analyzed using novel semi‐automated software designed for 3D measurements of the aortic root, which uses multiplanar reconstruction, similar to CT analysis. Aortic annulus measurements included area, perimeter, and diameter calculations from these measurements. The results were compared to CT‐derived values. Additionally, 3D echocardiographic measurements (3D planimetry and mitral valve analysis software adapted for the aortic valve) were also compared to the CT reference values. Results: 3DTEE image quality was sufficient in 90% of patients for aortic annulus measurements using the new software, which were in good agreement with CT ( r ‐values: .89–.91) and small (<4%) inter‐modality nonsignificant biases. Repeated measurements showed <10% measurements variability. The new 3D analysis was the more accurate and reproducible of the existing echocardiographic techniques. Conclusions: Novel semi‐automated 3DTEE analysis software can accurately measure aortic annulus in patients with severe AS undergoing TAVR, in better agreement with CT than the existing methodology. Accordingly, intra‐procedural TEE could potentially replace CT in patients where CT carries significant risk.